Optimizing Supply Chain Performance: A Performance Prism Analysis of Goods Receipt in Semiconductor Manufacturing - Simanjuntak, Shalini; Devano, Alrido Martha (Pusat P2M Politeknik Negeri Batam, 2025)
This study analyzes the goods receipt process performance at a semiconductor manufacturing company facing issues with process failures and inaccurate goods handovers, resulting in significant losses. Also, the company has never applied a comprehensive and structured performance measurement method to the goods receipt process. Using Performance Prism and Analytical Hierarchy Process (AHP) methods, 23 Key Performance Indicators (KPIs) were identified from three stakeholder groups: internal customers, receiving staff, and suppliers, categorized into five Performance Prism perspectives. Data collected through interviews was analyzed using Objective Matrix (OMAX) and Traffic Light System (TLS). Results show the current goods receipt process performance is in the yellow category, with a value of 3.66 and a score of 6, indicating adequate but improvable performance. The semiconductor manufacturing company needs to focus on enhancing KPIs in the yellow and red categories to achieve optimal performance. Recommendations include conducting periodic evaluations and improving communication systems between stakeholders to address these performance issues and minimize losses.